Forms of Antonyms in Semantics According to the Perspective of Muhammad Ali Al-Khuli (Studies of Qur’an Surah Ar-Rum) - Alamin, Nurul Salis; Anwar, Heru Saiful; Janah, Nafisah Nurul; Pambayun, Puspito (Study Program of Arabic Language Teaching, 2023)
This research explores one of the branches of science in semantics, namely Tadhad in the Arabic Language (Antonym). It also explains the various contradictions in Surah Ar-Rum and their classification based on the meanings that some interpreters interpreted in its verses. This type of research is qualitative research using a literature research approach. The data used in this study are antonym forms based on the perspective of Muhammad Ali Al-Khuli with the research data source, namely Surah ar-Rum. The data analysis technique that researchers use is in the form of documentation using content analysis. Researchers use this method to assist in achieving research goals. The result of this research is that there are nine types of antonyms. The antonymy words contained in Surah Ar-Rum amount to 17 verses. Of the 9 kinds of antonyms that exist, in these verses there are 4 kinds of antonyms, namely, Ungradable Antonym is found in verses 7, 19, 24, and 41, and Gradable Antonym is found in verses 8, 22, 25, 26, 36 and 54, Converseness Antonym is found in verses 6, 17, 23, 29 and 40, then the last one is Affinity Antonym contained in verse 18.